An optimized efficient dual junction InGaN/CIGS solar cell: A numerical simulation. (August 2016) - Farhadi, Bita; Naseri, Mosayeb
Abstract: The photovoltaic performance of an efficient double junction InGaN/CIGS solar cell including a CdS antireflector top cover layer is studied using Silvaco ATLAS software. In this study, to gain a desired structure, the different design parameters, including the CIGS various band gaps, the doping concentration and the thickness of CdS layer are optimized. The simulation indicates that under current matching condition, an optimum efficiency of 40.42% is achieved. Highlights: A new dual-junction InGaN/CIGS solar cell has been proposed. The structure materials have been optimized to gain a more efficient model. The sub-cells cell currents have been matched. The optimized energy conversion efficiency of 40.42% has been achieved.